Fisetin Attenuates Doxorubicin-Induced Cardiomyopathy In Vivo and In Vitro by Inhibiting Ferroptosis Through SIRT1/Nrf2 Signaling Pathway Activation - Li, Danlei; Liu, Xiaoman; Pi, Wenhu; Zhang, Yang; Yu, Lei; Xu, Cheng; Sun, Zhenzhu; Jiang, Jianjun (Frontiers in Pharmacology, 2022)
Doxorubicin (DOX) is an anthracycline antibiotic that is used extensively for the management of carcinoma; however, its clinical application is limited due to its serious cardiotoxic side effects. Ferroptosis represents iron-dependent and reactive oxygen species (ROS)-related cell death and has been proven to contribute to the progression of DOX-induced cardiomyopathy. Fisetin is a natural flavonoid that is abundantly present in fruits and vegetables. It has been reported to exert cardioprotective effects against DOX-induced cardiotoxicity in experimental rats. However, the underlying mechanisms remain unknown. The present study investigated the cardioprotective role of fisetin and the underlying molecular mechanism through experiments in the DOX-induced cardiomyopathy rat and H9c2 cell models. The results revealed that fisetin treatment could markedly abate DOX-induced cardiotoxicity by alleviating cardiac dysfunction, ameliorating myocardial fibrosis, mitigating cardiac hypertrophy in rats, and attenuating ferroptosis of cardiomyocytes by reversing the decline in the GPX4 level. Mechanistically, fisetin exerted its antioxidant effect by reducing the MDA and lipid ROS levels and increasing the glutathione (GSH) level. Moreover, fisetin exerted its protective effect by increasing SIRT1 expression and the Nrf2 mRNA and protein levels and its nuclear translocation, which resulted in the activation of its downstream genes such as HO-1 and FTH1. Selective inhibition of SIRT1 attenuated the protective effects of fisetin in the H9c2 cells, which in turn decreased the GSH and GPX4 levels, as well as Nrf2, HO-1, and FTH1 expressions. In conclusion, fisetin exerts its therapeutic effects against DOX-induced cardiomyopathy by inhibiting ferroptosis via the SIRT1/Nrf2 signaling pathway activation.